El modelo textual de Basilea y "en efecto" - Pura Guil Povedano (Philologia Hispalensis, 2014)
This paper’s goal is to offer an analysis of the Spanish item en efecto using a text model (Basel Model) that has been elaborated mainly on the basis of Italian language’s data. The analysis is based on assuming the hypothesis that the information value associated with a given linguistic expression plays a critical role in determining its function, scope and relief. Also the paper will seek to highlight the problems generated by the mismatched punctuation in Italian and Spanish, in terms of discursive markers.